The Teaching Model through Problem-Based Learning in a Course on Bibliographic Research - Hernández-Ching, Ruth Cristina (2018)
The experience of applying problem-based learning (PBL) technique in the Bibliographic Research course from a Bachelor of English study plan of a public university during the first half of 2014 is shared. The investigation aimed to answer the following question: Does the problem-based learning technique in the Bibliographic Research course allows to implement the main tenets of the teaching model: epistemological foundation, learning theory, methodology and didactics, and communication processes? The research approach proposed was qualitative, and triangulation for measuring variables was implemented. The following instruments were applied: observation, experience record books, and focus groups. Furthermore, formative learning was measured by means of an online survey. Results of the instruments were categorized using technology-based tools such as Wordle (observation), NVivo (record books) and MindNode (focus groups). A convenience sampling was used to collect data from eight students enrolled in the Bibliographic Research course, ten students of Integrated English II for non-English majors, and the researcher, as professor of the courses. It was determined that the PBL technique permitted to reach the main tenets of the teaching model. It was identified that the teacher was the main learner, and the one who benefited from the process, since a culture of knowledge, throughout the course, was created. It was also concluded that this technique allowed to develop twenty-first century skills. It would be valuable to quantify whether the development of the four basic skills of English, especially the conversation one, improves using the technique along with technologies.